PENGARUH BAURAN PEMASARAN DAN FAKTOR PSIKOGRAFIS DALAM MEMBENTUK PERILAKU PEMBELIAN MAHASISWA TERHADAP PRODUK BUAH POTONG KEMASAN - Dinar Putri Nurjahwa; Herawati Herawati (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2026)
Fruit consumption in Indonesia remains relatively low despite the continued growth of local fruit production. This condition indicates that low fruit consumption is not solely related to limited availability, but is also influenced by changing consumer preferences toward food products. This has encouraged the development of packaged fresh-cut fruit as an alternative way of consuming fruit that offers convenience and practicality, particularly for young consumers in urban areas who tend to prefer food products that are practical and easy to consume. This study aims to analyze the influence of the marketing mix and psychographic factors, including lifestyle and health consciousness, on students’ purchasing decisions regarding packaged fresh-cut fruit in modern retail. Primary data were collected from 170 undergraduate students of the Faculty of Economics and Management, IPB University, who had purchased and consumed packaged fresh-cut fruit from modern retail outlets. The data were analyzed using descriptive analysis, Partial Least Squares–Structural Equation Modeling (PLS-SEM), and Importance Performance Matrix Analysis (IPMA). The results show that students’ purchasing decisions are more strongly influenced by the marketing mix than by psychographic factors. The marketing mix, consisting of product, price, place, and promotion, has a positive effect on purchasing decisions, while lifestyle and health consciousness as psychographic factors have no significant effect. Modern retailers are therefore advised to prioritize affordable pricing, as it is the most important factor considered by student consumers when making purchasing decisions.